Transnational remittances and state protection of human rights: A case for caution. (24th April 2019) - Bang, James T.; Mandal, Arindam; Mitra, Aniruddha
Abstract: This paper explores the impact of transnational remittance receipts on state respect for human rights, identifying the latter with the CIRI Index of Physical Integrity Rights which aggregates information on disappearances, extrajudicial killings, political imprisonment, and torture. Based on sample of 106 developing economies considered over the period 1981–2011, we find that remittances have a strong negative impact on state respect for physical integrity rights, the results being robust to alternate specifications and estimation methods. Our results underline the need for caution in evaluating the developmental consequences of remittance inflows, especially on institutional quality.